Accumulation of Circulating Cell-Free CpG-Enriched Ribosomal DNA Fragments on the Background of High Endonuclease Activity of Blood Plasma in Schizophrenic Patients - E. S. Ershova; E. M. Jestkova; A. V. Martynov; G. V. Shmarina; P. E. Umriukhin; L. V. Bravve; N. V. Zakharova; G. P. Kostyuk; D. V. Saveliev; M. D. Orlova; M. Bogush; S. I. Kutsev; et al. (International Journal of Genomics)
Introduction. Schizophrenia (SZ) increases the level of cell death, leading to an increase in the concentration of circulating cell-free DNA (cfDNA). Ribosomal DNA (rDNA) contains many unmethylated CpG motifs that stimulate TLR9-MyD88-NF-κB signaling and the synthesis of proinflammatory cytokines. The number of rDNA copies in the genomes of SZ patients is increased; therefore, we expect that the concentration of cell-free rDNA in the plasma of the SZ patients also increases. This may be one of the explanations of the proinflammatory cytokine increase that is often observed in SZ. The major research question is what is the rDNA copy number in cfDNA (cf-rDNA CN) and its putative role in schizophrenia? Materials and Methods. We determined cfDNA concentration (RNase A/proteinase K/solvent extraction; fluorescent dye PicoGreen) and endonuclease activity (NA) of blood plasma (radial diffusion method) in the untreated male SZ group (N=100) and in the male healthy control group (HC) (N=96). Blood leukocyte DNA and cfDNA rDNA CN were determined with nonradioactive quantitative hybridization techniques. Plasma concentration of cf-rDNA was calculated. Results. In the subjects from the SZ group, the mean cfDNA plasma concentration was twofold higher and NA of the plasma was fourfold higher than those in the healthy controls. rDNA CN in the blood leukocyte genome and in the cfDNA samples in the SZ group was significantly higher than that in the HC group. cf-rDNA concentration was threefold higher in the SZ group. Conclusion. Despite the abnormally high endonuclease activity in the blood plasma of SZ patients, the circulating cfDNA concentration is increased. Fragments of cf-rDNA accumulate in the blood plasma of SZ patients. Potentially, SZ patients’ cfDNA should be a strong stimulating factor for the TLR9-MyD88-NF-κB signaling pathway.